Neuromuscular exercise and back counselling for female nursing personnel with recurrent non-specific low back pain: study protocol of a randomised controlled trial (NURSE-RCT). Issue 1 (3rd March 2016) - Suni, Jaana H; Rinne, Marjo; Kankaanpää, Markku; Taulaniemi, Annika; Lusa, Sirpa; Lindholm, Harri; Parkkari, Jari
Abstract : Introduction: Nursing personnel have high risk for incidence of low back pain (LBP) followed by development of chronic pain and disability. Multiple risk factors such as patient handling, night shift work and lack of supporting work culture have been identified. In subacute LBP, high-fear avoidance is prognostic for more pain, disability and not returning to work. Lack of leisure-time physical activity predicts long-term sickness absence. The purpose of this study is to compare effectiveness of 6-month neuromuscular exercise and counselling in treating back pain in female nursing personnel with recurrent non-specific LBP pain compared with either (exercise or counselling) alone and a non-treatment control group. Methods and analysis: The design is of a double-blinded four-arm randomised controlled trial with cost-effectiveness evaluation at 12 and 24 months. The study is conducted in 3 consecutive substudies. The main eligibility criteria are experience of LBP during the past 4 weeks with intensity of at least 2 (Numeric Rating Scale 0–10) and engagement in patient handling. Sample size was estimated for the primary outcome of pain intensity (visual analogue scale). Study measurements are outlined according to the model of International Classification of Functioning, Disability and Health, which incorporates the biopsychosocial processes assessed. Ethics and dissemination: This study is carried out conforming to the guidelines of good scientific practice and provisions of the declaration of Helsinki. Increasing physical and mental capacity with interventions taking place immediately after working hours near the worksite may reduce development of chronic LBP and work disability in female nursing personnel with recurrent non-specific LBP. Trial registration number: NCT04165698.